Building teachers' capacity for success [ a collaborative approach for coaches and school leaders - Hall, Peter A. , 1971-; Simeral, Alisa (Gale virtual reference library, 2008)
Focuses on building the capacity of teachers, supporting teachers to help them reach their potential, and making the best use of teachers' individual and collective contributions to school improvement efforts.